Stock Manipulation: The Case of the Taiwan Stock Exchange - Huang, Yu Chuan; Chen, Roger C. Y.; Cheng, Yao Jen (Indian Journal of Finance, 2008)
Using a new hand-collected data set, this study examines stock price manipulation in the Taiwan Stock Exchange. We examine the characteristics of the manipulated stocks and their impacts on market quality. The results show that (1) Manipulated stocks tend to be smaller, (2) stock prices rise throughout the manipulation period, followed by a price reversal, and (3) the average cumulative abnormal return of the manipulated stocks is over 70 percent, which is far higher than that found in the developed markets but similar to that found in emerging markets. In addition, manipulated stocks display increased return continuation and increased volatility of stock return-conditional on high trading activities during the manipulation period. Market depth is also worse during the manipulation period. This suggests that stock manipulation can actually create market inefficiency, lead to both abnormally high trading volume and volatility, worsen market depth, and hence have important impacts on market quality.